Unto This Last: John Ruskin and the Beginnings of English Ecocriticism - Jajtner, Tomáš (American & British Studies Annual, 2020)
The following paper deals with the beginnings of ecocritical thought in John Ruskin’s essay Unto This Last (1862). The article presents the context of its economic thought and relates it to the beginnings of “ecology” in the work of German biologist Ernst Haeckel (1834-1919). The key aspect of Ruskin’s approach is a close link between a humane economy and a sense of responsibility for the environment. In his sweeping analysis of laissez-faire capitalism, he contrasts creation with production, focuses on the reductive terminology of political economy and its potentially devastating consequences if it becomes the leading ideology of the state. The final part of the paper assesses the importance of this essay for the development of ecocritical thought as well as its relevance today.